Towards personalized intensive care decision support using a Bayesian network: A multicenter glycemic control study - Abu-Samah A.; Razak N.N.A.; Suhaimi F.M.; Jamaludin U.K.; Chase J.G. (Institute of Electronics Engineers of Korea, 2023)
Benchmarking; Decision support systems; Hospital data processing; Intensive care units; Patient treatment; Trees (mathematics); Blood glucose measurements; Classification precision; Discretization algorithms; Discretizations; Glycemic control; Performance prediction; Structure-learning; Variable selection; Bayesian networks